Understanding overuse injuries in rhythmic gymnastics: A 12-month ethnographic study. (July 2016) - Cavallerio, Francesca; Wadey, Ross; Wagstaff, Christopher R.D.
Abstract: Objectives: This study aimed to gain an in-depth understanding of overuse injuries in rhythmic gymnastics from a psychosocial perspective. More specifically, it examined how sport culture impacts overuse injuries. Design: To develop an understanding of the culture of rhythmic gymnastics and gymnasts' behaviour within the context of this culture, ethnography was the chosen method and written product of this research. Method: A 12-month ethnography was conducted in an elite rhythmic gymnastics club in Italy, with 43 participants, consisting of 16 gymnasts, three female coaches, one physiotherapist, 22 parents, and the club's president. Eight qualitative methods of data collection were used to provide rigor and depth. Following data transcription, a thematic analysis was conducted to identify the emergent themes. Findings are presented using ethnographic creative nonfiction for ethical, theoretical and practical reasons. Results: Two stories were created portraying the same training session through the eyes of a gymnast and her coach. The stories reflect the differences in the interpretation of the same situations and the cultural norms, values and behaviours that influenced the occurrence and experience of overuse injuries. Conclusions: This study extends research on overuse injuries in three ways: (a) it honours athletes as social agents by exploring the intersection between psychology and sociology, (b) it uses a rigorous methodology to elicit a more in-depth understanding of overuse injuries, and (c) it adopts an innovative form of representation to increase the accessibility of the findings to non-academic audiences. Highlights: Overuse injuries in rhythmic gymnastics are not only caused by physical factors. Cultural values and unwritten norms influence gymnasts' attitude towards pain. Mental toughness behaviours can have negative influences on gymnasts' health. Poor communication between gymnasts and coaches causes misunderstandings.